Un estudio desde lo social y lo económico de los homicidios en el Ecuador durante el periodo 1987-2020 - Guevara Méndez., Jhomayra Elizabeth (2024)
In Ecuador, during the year 2020, homicides represented a rate of 7.78% of violent cases due to family problems, micro-trafficking, threats, robberies, gangs, unemployment, among others. In this sense, the general objective of this research is to analyze the relationship between homicides and the main social and economic factors in Ecuador during the period 1987-2020. The data for the period analyzed were extracted from the World Bank, KOF, Penn World Table, Varieties of Democracy V-Dem; and econometric and statistical techniques for time series were applied. Among the most outstanding results, it was observed that the variables tend to undergo changes that vary over time. In addition, using the Newey-West model, an inverse relationship was found between the homicide rate and unemployment, while a positive relationship was found with income inequality. Subsequently, with the Vector Autoregressive (VAR) model, a long-term relationship was found between homicides and unemployment and income inequality. Finally, among the main recommendations, it is proposed the implementation of public policies aimed at providing greater security to society, through the application of education and training programs, especially aimed at the institutions in charge, young people at risk and victims of violence, which will allow them to obtain the necessary tools to break the cycle of violence.